Combustion Performance and Kinetic Analysis of Shenhua Raw Coal Mixed Coal Gasification Slag. Issue 1 (July 2020) - Wang, Yunfei; Zhang, Fushen; Zheng, Zhilei; Wang, Huiqi; wang, Feng
Abstract: In this paper, Shenhua coal and its gasification slag (GS) in Ordos are taken as the research objects. The thermogrmetric analyzer is used to investigate the mixed combustion characteristics of different proportions. The experimental results show that Shenhua raw coal mixed with GS can improve the overall ignition and burnout characteristics of mixed coal to some extent. With the increase of the mixing amount of GS, the combustion characteristic temperature of coal samples presents an overall trend of increase in ignition point temperature ( T i ) and burnout temperature ( T b ). When the GS content is 50%, the maximum weight loss temperature ( T max ) is the highest. The mixing amount of GS is not equal to the change of sample mass. The comprehensive combustion characteristic S decreases with the increase of GS content.When the mixing amount of GS was 50%, the minimum apparent activation energy obtained was 87.11kJ/mol.